2013
DOI: 10.1007/s00167-013-2455-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of a mono-fluted reamer results in decreased enlargement of the tibial tunnel when using a transtibial ACL reconstruction technique

Abstract: The use of a mono-fluted reamer for femoral tunnel preparation results in less tibial tunnel deformation during transtibial reaming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…A further study demonstrated differences in tibial tunnel deformation between reamer designs when reaming the femoral tunnel if a transtibial technique is used. 4 In our study, we noted that the dimensions of the tibial tunnel's outer aperture vary relative to the reamer's diameter, even when reaming was performed in line with the guidewire. We believe the likely explanation is that the reamer penetrates the outer cortical surface at an angle rather than perpendicular to it.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…A further study demonstrated differences in tibial tunnel deformation between reamer designs when reaming the femoral tunnel if a transtibial technique is used. 4 In our study, we noted that the dimensions of the tibial tunnel's outer aperture vary relative to the reamer's diameter, even when reaming was performed in line with the guidewire. We believe the likely explanation is that the reamer penetrates the outer cortical surface at an angle rather than perpendicular to it.…”
Section: Discussionmentioning
confidence: 71%
“…A further study demonstrated differences in tibial tunnel deformation between reamer designs when reaming the femoral tunnel if a transtibial technique is used. 4…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result indicates that those cases could incur damage to the MFC. A mono-fluted reamer 35 with an eccentric mono-fluted cutting edge and narrow shaft is useful to make the femoral tunnel and prevent MFC damage. We used the Sentinel cannulated reamer to prevent damage to the MFC cartilage.…”
Section: Complications Of Transportal Techniquementioning
confidence: 99%